Ambient ammonium exposure is associated with physical dysfunction in older adults in China - JiaHao Shi (Scientific Reports)
Abstract The health effects associated with particulate matter (PM) are extensively reported; nevertheless, limited research has explored the exact contributions of its chemical constituents to physical dysfunctional aging. This study assesses the relationships between prolonged exposure to significant ambient air pollutants, especially ammonium (NH4 +), and physical dysfunction in a nationally representative cohort of older Chinese adults. We investigated data from 14,641 participants aged 45 years or older in the 2015 wave of the China Health and Retirement Longitudinal Study (CHARLS), which was integrated with high-resolution air pollution data from the ChinaHighAirPollutants (CHAP) dataset. Physical dysfunction was evaluated by self-reported challenges in executing routine activities. After controlling for a wide range of confounders, associations among eight air contaminants (averaged from 2013 to 2015) and dysfunction risk were investigated using logistic regression models. Multicollinearity among covariates in the fully adjusted models was assessed using the generalized variance inflation factor (GVIF), with a threshold value of 5 adopted as the criterion to indicate potential collinearity. Sensitivity analyses—including exclusion of high-exposure participants, standardized z-score modeling, stratified subgroup evaluations, and multipollutant adjustments—were performed to assess the robustness of associations. Dose–response relationships were modeled using both quartile-based logistic regression and restricted cubic spline (RCS) models, revealing consistent and complementary trends. To estimate independent effects and address potential collinearity, we further constructed a multipollutant model adjusting for seven co-pollutants. In all and fully adjusted models, ambient ammonium (NH4 +) was the only air pollutant that demonstrated a significant and independent association with physical dysfunction (OR: 1.03; 95% CI: 1.01–1.05; p < 0.05); no significant associations were found for the other pollutants. This association remained robust across multiple sensitivity analyses, including exclusion of extreme exposure (OR: 1.13; 95% CI: 1.08–1.17; p < 0.001), z-score standardization (OR: 2.17; 95% CI: 1.57–2.98; p < 0.001), and 5 stratified subgroup models. A significant dose–response relationship was identified both in quartile-based trend tests (p for trend < 0.001) and restricted cubic spline analysis (p for non-linearity < 0.001). Taken together, the monotonic trend from quartile analysis and the non-linear pattern from spline modeling suggest that even moderate exposure to NH4⁺ may contribute to physical dysfunction. Furthermore, multicollinearity diagnostics based on generalized variance inflation factors (GVIFs) indicated no evidence of problematic collinearity among covariates in the fully adjusted models (all GVIF < 5). Besides, the association remained significant and became stronger in a multipollutant model, highlighting the independent effect of NH4 + beyond co-pollutant confounding (OR: 1.49; 95% CI: 1.26–1.76; p < 0.001). Our findings indicate that NH4 +, a significant secondary component of PM predominantly sourced from agricultural ammonia emissions, may uniquely contribute to the deterioration of physical function. It may be important to evaluate particle chemical makeup for analyzing health concerns, as there is no association for total PM mass. Long-lasting exposure to ambient NH4 + has been independently associated with increased odds of physical dysfunction across older adults in China. These findings underscore the necessity for specific environmental strategies focused on ammonia reduction to alleviate age-related functional deterioration and foster healthy aging.